Generation lengths of the world's birds and their implications for extinction risk - Jeremy P. Bird; Robert Martin; H. Reşit Akçakaya; James Gilroy; Ian J. Burfield; Stephen T. Garnett; Andy Symes; Joseph Taylor; Çağan H. Şekercioğlu; Stuart H. M. Butchart (Conservation Biology, 2020)
Birds have been comprehensively assessed on the International Union for Conservation of Nature (IUCN) Red List more times than any other taxonomic group. However, to date, generation lengths have not been systematically estimated to scale population trends when undertaking assessments, as required by the criteria of the IUCN Red List. We compiled information from major databases of published life‐history and trait data for all birds and imputed missing life‐history data as a function of species traits with generalized linear mixed models. Generation lengths were derived for all species, based on our modeled values of age at first breeding, maximum longevity, and annual adult survival. The resulting generation lengths varied from 1.42 to 27.87 years (median 2.99). Most species (61%) had generation lengths